The Analysis of Instagram Use as a Media of Tourism Promotion in Malang City (Case Study on @Amazingmalang Instagram Account) - Rashad, Alma Saquille; Asri, Tri Mega (Journal of Indonesian Tourism and Development Studies, 2020)
Today's social media use is very influential in the lives and perspectives of finding a wide variety of information. Most social media users prefer to use Instagram as an attractive information provider app with Visual media treats in the form of images and videos tourism industry that has undergone a lot of rapid progress. Like the city of Malang, it becomes the main tourist destination for tourism by foreign and foreign tourists when they want to go on holiday. This research discussed the success rate of Instagram as a tourism promotion media in Malang. This type of research is qualitative descriptive research. The data collection techniques used are three ways: interviews, questionnaires, and case studies. The results showed the success rate of tourism promotion in Malang City using the Instagram @amazingmalang.Keywords: Instagram, promotions, tourism.